O ensino de filosofia: análise da atuação educativa de êxito tertúlia dialógica buscando a autonomia discente na Escola de Tempo Integral - ANJOS, Daniela de Oliveira dos (2021)
This study aims to analyze the Educational Performance of Dialogical Literary Gathering in Philosophy that seeks the student autonomy in the Full Time School, as the education turns the student into a moral being, from a theoretical- methodological investigation that contributes with the development of the students’ autonomy at the Centro Educa Mais João Francisco Lisboa. Immanuel Kant educational theories indicate that if we want an education for transformation we must invest in teaching based on understanding and exercising autonomy. In this regard, Dialogical Literary Gathering comprehend an education for autonomy that conceives the students as characters inserted in the world, who relate to others and change themselves and the world. Kant bases himself on the critical- emancipatory principle that education is a necessary tool for human development. The education must rule over the child’s primal instincts, so that it does not deviate from the education project, in other words, it gives the condition to the student to become an autonomous individual. It is observed in Immanuel Kant’s literature the concepts of freedom, morals and discipline, brought in his work about Pedagogy when he offers us clear indicators on how to educate children so that we can have autonomous citizens in society. In this perspective, the relevance of teaching philosophy in basic education for the construction of the human being is emphasized, considering that this provides means for the understanding of that as a historical subject and participant in addition to knowledge of the world and himself. Therefore, the Dialogical Literary Gathering is a methodological proposal of education that includes the act of educating from the student’s reality, adding the formation of values for his life. For this reason, as well as the main thinker the following authors are taken as references: Marçal (2009), Apis (2007), Bresolin (2016), Cerletti (2009), Dalbosco (2011), Gatti (2019), Ghedin (2009), Flecha (1997), Gallo (2007), Freire (2019), Habermas (2012), Ranciére (2004), Rousseau (2014). For this matter, this dissertation is concerned in addressing on the first chapter the conception of Dialogical Literary Gathering, discussing its relevance to the autonomy. Expatiate about the historical aspects of education and dialogicity on the second chapter with Immanuel Kant, who places education as a guide for clarification, morality and finally the analysis of the locus and research methodology in the last chapter, where the results of our research will be done at the chosen school.